Cross-Cultural Configuration Evidence from International Business Organisation in ASEAN Countries - Meytra Taufik, Henry; Nasimov, Husein; Zulhazmi Abdul Rashid, Aimi (International Journal of Psychosocial Rehabilitation, 2020)
The study was designed to investigate the cross-cultural configurations in international organizations. The purpose of this research is to identify how cross-cultural affects a workplace environment, employees’ performance and individual performance. The dependent variable for this research is cultural differences in organization. The independent variables are employee behaviors, individual performance and workplace environment. In order to collect data from respondents, the researcher has used quantitative methods. To get the result, this research using IBM SPSS 16.0 to calculate the data that they receive. This study has successfully identified effect of cross-cultural towards the variables. The results of this research have shown that most of the respondents agreed that cross-cultural affect the performance and also working environment.